The Use of Modified Diets by adults with Temporomandibular Disorders: Systematic Review and Meta-analysis - Gilheaney, Orla; Kerr, Patrick; Walshe, Margaret (My University, 2018)
Statement of the Problem: Temporomandibular disorders (TMDs) are the most frequently reported non-dental orofacial pain disorders. Pain and dysfunction of the jaw joint and masticatory muscles may result in individuals modifying their diet to softer food options, which may not be nutritionally balanced and which may have a subsequent negative impact on physical functioning and psychosocial well-being. However, little is known about the extent of diet modifications or their use as a compensatory strategy in this group. Therefore, clinical guidance to ensure continued adequate oral intake which does not exacerbate masticatory impairments, increase parafunctional behaviours, or compromise quality of life is not available, with potential impact on the individual’s health, functioning, and psychosocial wellbeing. Purpose of the Study: The aim of this intervention review was to determine the prevalence of diet modification use in adults presenting with TMDs. Materials and Methods: A systematic review of available evidence was completed. Electronic databases searched from inception to January 2017, with no date/language restriction applied were: EMBASE, PubMed, CINAHL, Web of Science, Elsevier Scopus, Science Direct, AMED, The Cochrane Database of Systematic Reviews, and ProQuest Dissertations and Theses A & I. Additional searches of grey literature, conference proceedings, and reference lists were also conducted. Studies presenting original data regarding the prevalence of diet modifications among adults presenting with TMDs were included. Study eligibility and quality were assessed by 2 independent reviewers. Methodological quality was assessed using the Down’s and Black assessment tool. Results: This search yielded 5 eligible studies. Diet modification use was reported by 45% of adult patients with TMDs (confidence interval: 31.93-58.64). Eligible studies were rated on average to be of moderate quality. Study limitations included the few studies which met the inclusionary criteria. Conclusions: Despite reported high levels of texture modified diet use among adults with TMDs, little information exists on the typical methods of modification, the content of the diets consumed, or the impact of these diets on systemic health and psychosocial well-being. In addition, it is unclear if these patients typically have access to dietitians during TMD management. Therefore, further research is required in order to examine the true dietary intake of individuals with TMDs and to subsequently determine the most appropriate methods of supporting these individuals to maintain healthy and balanced levels of oral intake.
PUBLISHED
Keywords: Dysphagia; Swallowing disorders; Deglutition; Diet modifications; Temporomandibular joint disorders; Ageing; Immunology, Inflammation & Infection; Age-related disability; Chronic Health Condition; Other